Invincible [compact disc, unabridged] - Palmer, Diana (Palmer, Diana. Long, tall Texans series., 2014)
Mercenary by name and nature, Carson is a love 'em and leave 'em kind of man. He enjoys shocking his friend Cash's innocent secretary, Carlie, with tales of his debauchery. Then Carlie sees something she shouldn't have and becomes the key witness who could implicate a popular politician in a murder case. Her only protection is Carson, but when she learns that Carson is more than just a tough guy, Carlie realizes she's in more peril. Now she could lose her heart to the most dangerous kind of man.